2017
DOI: 10.1161/circep.116.004915
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Vein Isolation Alone Versus Additional Linear Ablation in Patients With Persistent Atrial Fibrillation Converted to Paroxysmal Type With Antiarrhythmic Drug Therapy

Abstract: Background-Atrial fibrillation (AF) type can vary depending on condition and timing, and some patients who initially present with persistent AF may be changed to paroxysmal AF after antiarrhythmic drug medication and cardioversion. We investigated whether circumferential pulmonary vein isolation (CPVI) alone is an effective rhythm control strategy in patients with persistent AF to paroxysmal AF. Methods and Results-We enrolled 113 patients with persistent AF to paroxysmal AF (male 75%, 60.4±10.1 years old) who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 51 publications
(55 reference statements)
0
18
0
Order By: Relevance
“…20 For the patients who improved from persistent AF to paroxysmal AF, however, after using AAD, additional linear ablation after CPVI did not affect outcome. 21 For the patients with longstanding persistent AF, additional CFAE ablation after CPVI plus linear ablation did not improve the rhythm outcome. 22 In this study, the rate of procedure-related complications was higher in the female patients than in male patients.…”
Section: Star-af2 and Extra-pv La Ablationmentioning
confidence: 90%
“…20 For the patients who improved from persistent AF to paroxysmal AF, however, after using AAD, additional linear ablation after CPVI did not affect outcome. 21 For the patients with longstanding persistent AF, additional CFAE ablation after CPVI plus linear ablation did not improve the rhythm outcome. 22 In this study, the rate of procedure-related complications was higher in the female patients than in male patients.…”
Section: Star-af2 and Extra-pv La Ablationmentioning
confidence: 90%
“…Although the PVI is an essential treatment of AF, the isolation of a large area around both ipsilateral PVs has been considered to be more effective in treating AF, and although the empirical isolation of the LAPW is categorized as class IIb and has not been recommended for during the initial ablation procedure, the LAPW could be a target in the strategy of catheter ablation, especially for persistent AF . On the other hand, the second‐generation CB has been generally utilized for the PVI, but the isolated area could be smaller compared to the conventional PVI using RF energy in a “point‐by‐point” fashion .…”
Section: Discussionmentioning
confidence: 99%
“…We have to take the possibility of esophageal injury into account when we perform the LAPW ablation according to a previous report. 12 An AEF is the most serious complication regarding the PVI procedure, and its incidence is reported to be 0.016-0.6% of AF ablation cases with RF energy. 16,17 AEFs after the PVI with the CB are also reported as an extremely rare complication which happens in 11 out of 120,000 patients.…”
Section: Serious Adverse Events Affecting the Esophagus Associated Wimentioning
confidence: 99%
“…Linear ablation approaches may include additional ablation lines at the mitral isthmus or the roof of the left atrium; for example, Kottkamp et al (2002) applied lesion lines from the mitral valve annulus to the pulmonary vein orifices to prevent anatomical reentrant circuits. Yu et al (2017) demonstrated that linear lesions together with PVI demonstrate similar efficacy to PVI alone. Other anatomical approaches include box isolation, which includes additional ablation lines to isolate a box of tissue on the posterior wall and roof, and aims to reduce the spatial size of the atrial substrate, where fibrillatory wavefronts may persistently propagate (Hwang et al, 2015;Williams et al, 2019).…”
Section: Introductionmentioning
confidence: 94%